Clean Technology Fund Investment Plan Approved for Concentrated Solar Power in the MENA Region - Coma-Cunill, Roger (World Bank, Washington, DC, 2012)
The Middle East and North Africa (MENA) clean technology fund investment plan proposes co-financing of $750 million and mobilizes an additional $4.85 billion from other sources to accelerate deployment of Concentrated Solar Power (CSP) by investing in the CSP expansion programs of Algeria, Egypt, Jordan, Morocco and Tunisia. Specifically, the Investment Plan will support MENA countries to achieve their development goals of energy security, industrial growth and diversification, and regional integration. The international energy agency has identified concentrating solar power (CSP) as one of the key technologies that 'are at the heart of the energy technology revolution because they can make the largest contributions to reducing greenhouse gas emissions.' However, CSP (like most new technologies) has higher costs and risks than current technologies. Therefore, international collaboration is required to accelerate the global deployment of technologies like CSP through targeted schemes providing positive incentives for their adoption at scale.